Analysis of Competition Maps, Service Quality, and Customer Movement Behavior of Internet Service Providers in the Special Region of Jakarta - Hanif Yusuf; Eko Ruddy Cahyadi; Alim Setiawan Slamet (Jurnal Doktor Manajemen (JDM), 2026)
This study aims to analyze the competitive map, service quality, and customer transfer behavior in four main internet service providers in the Special Region of Jakarta, namely IndiHome, Biznet, First Media, and MyRepublic. Internet services, which have become an essential need of urban communities, present fierce competition between providers, especially in terms of speed, stability, price, and user experience. This study uses the Multidimensional Scaling (MDS) method to map the brand position based on customer perception of service attributes, including features, network reliability, area coverage, speed, and price. In addition, the Kano model is used to assess the level of customer satisfaction with each service attribute, while the Markov Chain method is applied to predict the chances of customer switching between service providers. The results show that Biznet occupies the most differentiated position with advantages in terms of speed and network stability, while IndiHome, First Media, and MyRepublic are in close positions which reflects the perception of service similarity in the minds of customers. These findings confirm that competitive advantage in the internet service provider industry is not only determined by price, but also by technical quality, reliability, and customer experience. Theoretically, this study strengthens the understanding that customer switching behavior is closely linked to perceived service quality and competitive positioning in service-based industries.This research is expected to be a reference for internet service providers and regulators in formulating strategies to improve service quality, customer retention, and encourage the creation of healthy market competition in the Indonesian telecommunications sector.